X-ray probe development for collective scattering measurements in dense plasmas - Urry, M; Gregori, G; Landen, O; Pak, A; Glenzer, S (2006)
X-ray spectra and conversion efficiencies of the laser-produced chlorine Ly- α and K- α line radiation have been investigated to develop X-ray probes for the collective scattering regime. The Ly- α radiation was produced by either smoothed or un-smoothed laser beams with nanosecond-long laser pulses yielding high conversion efficiencies of up to 0.3% sufficient for X-ray scattering measurements. However, the time-integrated measurements show a significant dielectronic satellite emission on the red wing of the primary Ly- α line which must be avoided to resolve the plasmon feature in the scattering spectra. We find no red wing emission features for ultra-short pulse laser produced K-α radiation. The bandwidth of ΔE/E = 2 × 10-3 is suited for collective scattering, but the conversion efficiency falls short of the high values achieved for the Ly-α. These findings indicate that present laser-produced X-ray sources will restrict the choice of detectors and plasma conditions for collective X-ray scattering from dense plasmas.